CREATIVE PROBLEM SOLVING AND PROCESS SKILLS IN INTEGRATED SCIENCE LEARNING - Lusia Beti Sumarni; Fahmi Fahmi; Eko Wahyuningsih (Program Studi Pendidikan IPA, Universitas Lambung Mangkurat, 2024)
Science learning has an important role in helping the development of intelligence for critical thinking, in the intellectual (cognitive), affective and psychomotor aspects of students. The creative problem solving model is a variation of learning with problem solving through systematic techniques in organizing creative ideas to solve a problem followed by strengthening process skills. The creative problem solving model with process skills is in accordance with the characteristics of students to investigate, try, and experiment. This learning activity is intended to foster students' abilities in using students' process skills, and students are able to become critical and independent thinkers, involving activities such as analyzing, synthesizing, making considerations, creating, and applying new knowledge to real-world situations.Keywords: Science learning, creative problem solving model, process skills. Pembelajaran IPA mempunyai peranan penting dalam membantu perkembangan kecerdasan untuk berpikir kritis, pada aspek intelektual (kognitif), afektif dan psikomotorik peserta didik. Model creative problem solving merupakan variasi pembelajaran dengan pemecahan masalah melalui teknik sistematis dalam mengorganisasikan ide-ide kreatif untuk menyelesaikan suatu masalah yang diikuti dengan penguatan keterampilan proses. Model creative problem solving dengan keterampilan proses sesuai dengan karakteristik peserta didik untuk menyelidiki, mencoba, dan bereksperimen. Kegiatan pembelajaran ini dimaksudkan untuk menumbuhkan kemampuan peserta didik dalam menggunakan keterampilan proses peserta didik, dan peserta didik mampu menjadi pemikir kritis dan mandiri, yang melibatkan kegiatan-kegiatan seperti menganalisis, mensintesis, membuat pertimbangan, menciptakan, dan menerapkan pengetahuan baru pada situasi dunia nyata.Kata kunci: Pembelajaran sains, model pemecahan masalah kreatif, keterampilan proses.